The improvement of germination method for producing the germinated brown rice using a water spraying system with a revolved sieve - Chungcharoen, Thatchapol; Sansiribhan, Sansanee; Munsin, Ronnachart; Phetpan, Kittisak; Fonghiransiri, Surasak; Limmun, Warunee (Engineering and Applied Science Research, 2024)
Water soaking is an important method in germinated brown rice (GBR) production that causes fermentation, leading to an unpleasant smell of GBR. In this research, a water spraying system with a revolved sieve is applied to produce the GBR. The increased speed and time of spray break led to higher moisture content and water absorption. The spray break of 30 min and revolved speed of 15 rpm provided the shortest time to obtain the paddy with a moisture content of 30% (w.b.). The incubation pattern with a revolved sieve and water spray provided the shortest incubation time for 90% germination. When producing the GBR with a water spraying system with a revolved sieve (GBR-WSSRS), it had a lower number of microorganisms compared to the GBR with a water soaking (GBR-WS), leading to higher scores of overall acceptability. However, the GBR-WSSRS had a lower GABA content than the GBR-WS.